PENGARUH LAMA WAKTU ANODISASI TERHADAP KEKERASAN ALUMINIUM HASIL ANODIZING - Aunur Rofiq; Margianto Margianto; Unung Lesmanah (UNIVERSITAS ISLAM MALANG, 2013)
When positioned as a metal anode in an electrolysis process with acid electrolyte will generally be discharged corroded. This corrotion is caused because the metal is oxidized and dissolfes oxidation results in the electrolyte. How ever different if the metal is aluminium, niobium, tantalum, titanium, tungste or zirconium and electrolyt that used when electrolysis is diprotic acid such as sulfuric acid, phospate acid or chromic acid. Metal-metal will still be oxidized but is a result of oxidation of the oxide layer is not soluple in the electrlyt but rather sticks to the surface of the metal logam oxida actually very use full inte engineering bacause the oxide layer will provide protective and decorative properties and the metal. Anodizing aluminium is commonly used for decorative purposes in order to in crease the sale value or attrate anthusiasts at an aluminium produc, but the anodizing machine technique also widely used for the purpose of improving the mecanical properties of aluminium that has a low hardness (abourt 450 Hv). Anodizing process is done through a process of electrolysis which is influenced buy several conditions so that all the conditions of the electrolysis process can affect the out come anodizing.